ANALYSIS OF CONCEPTS UNDERSTANDING AND STUDENTS' ATTITUDES TOWARDS LEARNING PHYSICS IN PARABOLIC MOTION AT SMAN KOTA PARIAMAN - Siti Fauziah; Fatni Mufit; - Ramli; Renol Afrizon; Zaitul Hidayat (Universitas Negeri Padang, 2021)
Understanding the concepts and attitudes of students is one of the essential things in learning. Based on previous researchers’ research, many students have low conceptual understanding or high misconceptions. In addition, students' attitudes towards learning physics are also considered less good. This study aims to determine: 1) students' conceptual understanding of the parabolic motion material, 2) students' attitudes towards learning physics, and 3) the relationship between conceptual understanding and student attitudes towards learning physics.This study uses a quantitative descriptive method. The sample consisted of 81 students from 3 high schools in Kota Pariaman, representing low, mediu, and high-level schools. The research instrument was in the form of a four-tier multiple-choice concept test about parabolic motion and a questionnaire about students' attitudes towards learning physics. The data analysis technique used is a combination of answers for the concept test and Likert Scale scoring to analyze the questionnaire. The relationship between conceptuaal understanding and attitude was analyzed using Pearson's product-moment correlation.The results showed that students experienced more misconceptions with a fairly high percentage (42,6-72,3). The results of the student attitude questionnaire showed that the indicators of student social implications had the highest percentage (72.3-77.4), and pleasure in learning physics had the lowest percentage (64.8-66.1). The relationship of understanding of concept with te attitude of the student using product moment correlation with a 5% significance three level for high school category show a moderate show a medium correlation and weak correlation with a positive relation of meaning that if the student’s attitude rose then the understanding of the concept of student will also rise or increase as well as otherwise. For students' attitudes, who found that the students' social implication indicators had a higher percentage and the pleasure in learning physics had a lower percentage. Regarding the relationship between attitudes and understanding of students' concepts, there is a moderate correlation, which means that students' attitudes also influenced students' understanding